A Prospective Audit of Desflurane Anaesthesia in the University of Malaya Medical Centre day Surgery Unit - Chiu, C.L.; Mansor , M.; Wang, C.M. (Faculty of Medicine, University of Malaya, 2005)
Observational audit in the University of Malaya Medical Centre Day Surgery Unit. Fifty ASA I-II unpremedicated day surgery patients received fentanyl and propofol induction after preoxygenation. Desflurane was introduced initially at 2% and the concentration was increased gradually to 4%, then 6%, 8% and 10% in nitrous oxide and oxygen. Patients breathed spontaneously throughout the surgery. Desflurane was switched off at the end of surgery and patients reathed 100% oxygen. The haemodynamic effect, perioperative complications and recovery profiles were recorded. Systolic arterial pressure and heart rate decreased after induction of anaesthesia but returned to baseline value at discharge. Adverse airway event such as coughing and postoperative nausea and vomiting are two unwanted complications